Caveolin-1 expression predicts efficacy of weekly nab-paclitaxel plus gemcitabine for metastatic breast cancer in the phase II clinical trial - Zhao, Yannan (BMC Cancer, 2018)
BACKGROUND: Nanoparticle albumin-bound (nab)-paclitaxel has better efficacy, safety profiles, and no need to use prophylactic steroids compared with solvent-based paclitaxel. We performed a single arm, phase II study to evaluate the efficacy and safety of weekly nab-paclitaxel and gemcitabine combination in patients with metastatic breast cancer (MBC) and explored role of tumor/stromal Caveolin-1 (Cav-1) as a predictive biomarker for the efficacy. METHODS: Nab-paclitaxel (125 mg/m(2)) and gemcitabine (800 mg/m(2)) were administered on days 1, 8, and 15 in a 4-week cycle. The primary end point was objective response rate (ORR). Secondary end points were progression free survival (PFS), overall survival (OS) and safety profile. Exploratory study included immunohistochemical detection of Cav-1. RESULTS: Among 85 patients enrolled in the study, ORR was 52.4%. After a median follow-up of 17.2 months, median PFS was 7.9 months (95%CI, 6.6–9.2) and median OS was 25.8 months (95% CI, 20.4–31.1). The most common toxicities were neutropenia (75.0% for all grades; 45.2% for grade 3 or worse) and the most common non-hematologic toxicity was peripheral neuropathy (50.0% for all grades, 7.14% for grade 3 or worse). Higher tumor Cav-1 level and lower stromal Cav-1 level were significantly associated with longer PFS of nab-paclitaxel and gemcitabine. CONCLUSIONS: The regimen had substantial antitumor activity and was well tolerated in MBC patients. Tumor/stromal Cav-1 level may be a good predictor for the efficacy of nab-paclitaxel and gemcitabine. TRIAL REGISTRATION: NCT01550848. Registered 12 March 2012. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12885-018-4936-y) contains supplementary material, which is available to authorized users.